A Comprehensive Review of Nanomaterials: Types, Synthesis, Characterization, and Applications (Biointerface Research in Applied Chemistry, 2023)
Nanotechnology has infiltrated all sectors due to its unique and evident impacts, which give the scientific community numerous breakthroughs in the medical, agricultural, and other domains. Nanomaterials (NMs) have risen to prominence in technological breakthroughs due to their adjustable physical, chemical, and biological characteristics and superior performance over bulk equivalents. NMs are divided into many categories based on size, composition, capping agents, form, and origin. The capacity to forecast NMs' unique features raises the value of each categorization. As the manufacturing of NMs and industrial uses grow, so does their demand. The purpose of this review is to compare synthetic and naturally occurring nanoparticles and nanostructured materials to determine their nanoscale characteristics and to identify particular knowledge gaps related to the environmental application of nanoparticles and nanostructured materials. The paper review includes an overview of NMs' history and classifications and the many nanoparticles and nanostructured materials sources, both natural and manufactured. Furthermore, the many applications for nanoparticles and nanostructured materials.